Palaeoenvironmental implications of a marine geoarchaeological survey conducted in the SW Argosaronic gulf, Greece. (April 2017) - Geraga, M.; Papatheodorou, G.; Agouridis, C.; Kaberi, H.; Iatrou, M.; Christodoulou, D.; Fakiris, E.; Prevenios, M.; Kordella, S.; Ferentinos, G.
Abstract: A marine geoarcheological survey was conducted at the southwestern end of the Argosaronic gulf in Greece, an area of archaeological importance. The survey was initiated by the discovery of a Late Bronze Age (LBA) shipwreck off Modi Islet. The survey which employed echo-sounding, sub-bottom profiling, side scan sonar systems and sediment coring extended to the area between Poros Island, Modi Islet and Argolid peninsula, aiming to evaluate the changes of the coastal zone extent in the past. The evolution of the palaeo-shoreline over the last 20 ka is proposed based on the interpretation of the acquired bathymetric and seismic records, the estimation of the thickness of the marine sediments and the examination of existing datasets of the relative sea level changes in the area. The produced scenarios suggest that major changes marked the extent of the coastal zone since the Paleolithics. During the Upper Paleolithic period, the coast was larger by at least 11 km 2 and Poros and Modi islands were connected to the Peloponnesus. The sea level rise during the Mesolithic period formed a well-protected bay between Poros Island and Peloponessus and disconnected the Modi Islet from Poros Island. The coastal zone reached the present configuration around Late Bronze Age. The detection and mapping of scarps on the seismic profiles imply that the sea level rise presented standstills at least from the Last Glacial maximum until the onset of Holocene. However, the submerged coasts could be potential areas of archaeological interest since the examined area is habited continuously from the Paleolithic period. The acoustic data sets produced high resolution geomorphological maps at the wreck site which constitute data base for the monitoring of the site. In addition, the examination of the seafloor texture at the wreck site suggests that the seafloor characteristics were unfavorable for the preservation of the shipwreck. Highlights: Marine geoarchaeological survey was conducted at the SW Argolid gulf, Greece. Echo-sounding, profiling, side scan sonar and short sediment coring were employed. Surveying included the site of a Late Bronze Age shipwreck off Modi Islet. The evolution of the paleo-shoreline since Paleolithic period was evaluated. Climatic changes and possible tectonism affected the coastal evolution.